Передача изображения в реальном масштабе времени в космической системе оптико-электронного наблюдения - Пашков, Д.П. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2011)
One of the ways to increase transfer rates of spectral images in the channel is to use data compression. To improve the efficiency of transmission of real-time compression techniques are used except in special complex airborne systems are used parallel processing of image blocks. This direction is considered in this article.